Entre rios e árvores da Universidade Federal do Pará: relações sociedade-natureza como base para Educação Ambiental em Belém, Pará - SILVA, Vanice Carvalho (2024)
Since the industrial revolutions, regarding the urbanization processes, society-nature relations have been undergoing reconfigurations in an increasingly accentuated dynamic. The distance between people and the environment is notable, associated with countless processes of socio-environmental degradation. Faced with this problem, the general aim of this study is to understand how society-nature relations can serve as a basis for Environmental Education practices in the Amazonian context of the Federal University of Pará (UFPA). The methodology adopted comprises on-site observations and 24 semi-structured interviews in three places on the banks of the Guamá, Tucunduba and Sapucajuba rivers, describing these places and analyzing how people perceive and relate to rivers and trees in their daily lives, identifying the level of interaction and knowledge of these social subjects in relation to these natural elements of the landscape. The results show that there is a paradoxical relationship between society and nature, with both rational and emotional demonstrations. On the one hand, there is a positive perception of the significance and importance of rivers and trees, with certain feelings of belonging. On the other hand, there is a tendency towards utilitarian values, with relationships of interest in natural resources, as well as a negative perception of environmental degradation. This perspective is evidenced by the low level of interaction/generalized knowledge about rivers and trees. In this sense, the role of Environmental Education is discussed from the conceptual and epistemological bases of Cultural and Humanistic Geography, with phenomenological approaches. Finally, it is considered that environmental education, based on local social and ecological contexts, is essential for promoting a critical and sustainable awareness in the Amazonian context, including local diversities and particularities.